1972
DOI: 10.1073/pnas.69.8.2052
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Relationships among the Variable Regions of Immunoglobulin Heavy Chains from Various Mammalian Species

Abstract: Immunoglobulin heavy chains of myeloma proteins from dogs and cats have been subjected to automated sequence analysis. When the results were compared with human heavy-chain sequences, all the dog and cat proteins could be unequivocally assigned to the VHIII subgroup. This pattern contrasts with that in human proteins in which only 25% of all heavy chains sequenced belong to this subgroup. The 30 residues at the NH2 termini of dog, cat, and human heavy chains had sequence identities near or exceeding 90%, in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1973
1973
1978
1978

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…The heavy chain result in the opossum (a pouched mammal) assumed particular interest because, although the sequence of the first 11 residues of the pool showed unequivocally that this preparation was assignable to the Vmii subgroup, the residue at position 2 was an isoleucine rather than the valine that is characteristic of VlcIIII proteins (30,13). This undoubtedly represents a "phylogenetically associated" residue (10) and merits further analysis in other members of the Metatheria.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The heavy chain result in the opossum (a pouched mammal) assumed particular interest because, although the sequence of the first 11 residues of the pool showed unequivocally that this preparation was assignable to the Vmii subgroup, the residue at position 2 was an isoleucine rather than the valine that is characteristic of VlcIIII proteins (30,13). This undoubtedly represents a "phylogenetically associated" residue (10) and merits further analysis in other members of the Metatheria.…”
Section: Discussionmentioning
confidence: 99%
“…For example, position 11 in rabbit kappa chains from homogeneous antibodies has generally been valine, while mouse and human kappa chains contain leucine at this position. The identification and interpretation of such residues have been complicated by the difficulty of specifying precisely what is implied by the terms "species specific" or "phylogenetically associated" (10). The residues in question a~e rarely, if ever, unique to a given species but are more accurately associated with broader level phylogenetic groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Each has an unblocked aminoterminal (Glu or Asp), which is characteristic of human VH sequences of the VHIII subgroup (21)(22)(23), and it has been suggested that this subgroup may be the predominant one in some nonprimate species (24). However, the sequences of VH173 and VH315 differ markedly; the two are only 40% homologous and they differ by at least two sequence gaps (Fig.…”
mentioning
confidence: 99%